THE IMPACT OF SOCIAL SUPPORT AND SELF-EFFICACY ON ACADEMIC STRESS AMONG MASTER'S STUDENTS IN ISLAMIC RELIGIOUS EDUCATION, CLASS OF 2024, SULTAN AGUNG ISLAMIC UNIVERSITY, SEMARANG - Irfan, Alif; Choeroni; Muchtar, Asmaji (Pedagogic Research-Applied Literacy Journal, 2025)
This study aims to determina the influence of social support and self efficacy on academic stress of islamic religion education master student class of 2024 who working on theses at Sultan Agung Islamic University, Semarang. The method used in this study is quantitatif with sample of 100 students. Data collection was carried out using a closed questionnaire.The result of the T test showed that the significance value for sosial support (X1) was 0,000 and self eficacy (X2) was 0,001, both of which were less than 0,05, so it can be concluded that there is a significant influence of both variables on academic stress. The T value for sosial support is 7,272 and for self efficacy is 3,239, which is greater than t table (1,98472), confirming the positive influence of both variables on academic stress. In addtion, the F test show that the significance value of 0,000 and the F value of 43,490 are greater than f table of 3,09, indicating that social support anda self efficacy simultaneously influence academic stress.